Understanding Parental Ethnotheories and Practices About Healthy Eating: Exploring the Developmental Niche of Preschoolers. Issue 5 (June 2019) - Srivastava, Deepa; Torquati, Julia; de Guzman, Maria Rosario T.; Dev, Dipti A.
Purpose: To understand parental ethnotheories (ie, belief systems) and practices about preschoolers' healthy eating guided by the developmental niche framework. Design: Qualitative hermeneutic phenomenology. Setting: Home. Participants: Participants were 20 parents of preschool-age children ages 3 to 5 years, recruited from a quantitative investigation. A majority of the participants were white, female, married, well educated, and working full time. Methods: Participants who completed the quantitative survey were asked to provide their contact information if they were willing to be interviewed. From the pool of participants who expressed their willingness to participate in the interviews, 20 participants were selected using a random number generator. In-person semistructured interviews were conducted until data saturation (n = 20). Thematic analysis was performed. Results: Three themes and 6 subthemes emerged: theme 1 —parental ethnotheories about healthy eating included subthemes of knowledge about healthy eating, motivations to promote healthy child development through healthy eating, and sources of knowledge about healthy eating (eg, doctors, social media, government guidelines, positive family-of-origin experiences); theme 2 —parental ethnotheories that supported organization of children's physical and social settings included structured mealtime routines and food socialization influences (eg, grandparents, siblings, and childcare programs); and theme 3 —parental ethnotheories that supported children's learning about healthy eating included parent–child engagement, communication, and encouragement in food-related activities (eg, meal preparation, visiting farmer's market, grocery shopping, gardening, cooking, baking). Conclusion: Findings advance the literature on parental practices about healthy eating. Parental ethnotheories (eg, beliefs, motivations, knowledge, and skills) matter. Developmental niche of preschoolers (ie, physical and social settings, childrearing practices, and parental ethnotheories) constitutes an interactive system in which ethnotheories serve as guides to parental practices. Fostering nutrition education and parent–child engagement, communication, and encouragement in food-related activities are recommended to promote children's healthy eating in daily routines.